PENERAPAN STRATEGI GENIUS LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI SMA NEGERI 2 SIAK HULU - Dini Meici; Rasmiwetti '; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to know the improve of students learning achievement by using Genius Learning strategy on the topic of the colloid in class XI science senior high school 2 Siak Hulu. This research was experimental research with pretest-postest design. The sample of this research were students of class XI science 4 as the experimental research and students of class XI science 3 as a control class that has been randomly selected after a test of normally and homogenity test. Experiment class is a class that is applied Genius Learning strategy while the control class was not. Data analysis technique used is t-test. Based on analysis of the data obtained tcount > ttable is 1,89 > 1,67, it is mean that the apllication of Genius Learning strategy can improved students learning achievement on the topic of the colloid in class XI science senior high school 2 Siak Hulu. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,79. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,68. Genius Learning strategy can activate the students in learning process to improve the students achievement in learning.Keywords : Learning Achievement, Genius learning, colloid